Capital expenditure and economic growth: A disaggregated analysis for Nepal - Ramesh Paudel (Cogent Economics & Finance, 2023)
This paper, using the most recent dataset, examines the government expenditure's effects on the economic growth of Nepal. In doing so, a particular focus is made on disaggregated government expenditures to identify the importance of sector-specific public expenditure. The methodology adopted in this paper considers the scenario of government budget constraints while allocating resources in specific sectors and attempts to find the elasticity of those expenditures in the country's economic growth. The results from the estimation employing Auto-regressive distributed lag (ARDL) approach to cointegration for the data from 1981 to 2020 are threefold. First, both capital and current expenditures in aggregate forms are not the contributors to economic growth unlike our assumption that capital expenditure is more important than current expendtirue for economic grwoth. Second, spending more on education, either in the form of capital or current expenditure, would make a meaningful contribution to accelerating economic growth. Third, the public expenditure in the health sector should be very rational, focusing more on capital health expenditure rather than spending current health expenditure. Therefore, the primary policy recommendation from this study is that Nepal should invest more in education and health. Moreover, spending on education to expand the area with wider coverage and quality logistics and infrastructure are both important, while such expenditure in health is to be focused on solid health logistics and infrastructures.
Keywords: O13; Q33; Q38; 330; Nepal; economic growth; capital expenditure